Study on genetic transformation of Zea mays with drought-responsive OsNAC45 gene - Phuong, Nguyen Duy; Hang, Pham Thu; Quyen, Cao Le; Huong, Bui Thi Thu; Hue, Huynh Thi Thu; Hoi, Pham Xuan (Vietnam Journal of Biotechnology, 2018)
Plants response to abiotic stresses by initiating a series of processes including the activation of transcription factors that can regulate expression of various stress-responsive and adaptive genes. NAC family (NAM, ATAF1/2, CUC2), which is the largest plant transcription factor family, plays an important role in the development and stress responses of plants. OsNAC10 gene fragment has 1080 nucleotide containing an open reading frame (OFR) encoding for protein OsNAC45.  OsNAC45is expressed predominantly in roots and leaves and induced by drought, high saliniy, low temperature and abscisic acid. Overexpression of OsNAC45in rice increased the plant tolerance to drought and high salinity. In this study, recombinant expression vector containing OsNAC45-encoding sequence under the control of the Arabidopsis stress-inducibleRd29Apromoter was designed and successfully transformed into model maize plants via Agrobacterium tumefaciens bacteria. The genotype of regeneration plants was identified by PCR and Real-time pPCR. Using semi-quantitative RT-PCR, the expression of transgene OsNAC45 in some T0 transgenic plants were detected. These results provide a basis for the study of the function of OsNAC45 in drought responses and for the development of drought stress tolerant crops.